Activation of β2-adrenergic receptors in microglia alleviates neuropathic hypersensitivity in mice - Damo, Elisa; Agarwal, Amit; Simonetti, Manuela (Cells, 2023)
Drugs enhancing the availability of noradrenaline are gaining prominence in the therapy of chronic neuropathic pain. However, underlying mechanisms are not well understood, and research has thus far focused on α2-adrenergic receptors and neuronal excitability. Adrenergic receptors are also expressed on glial cells, but their roles toward antinociception are not well deciphered. This study addresses the contribution of β2-adrenergic receptors (β2-ARs) to the therapeutic modulation of neuropathic pain in mice. We report that selective activation of β2-ARs with Formoterol inhibits pro-inflammatory signaling in microglia ex vivo and nerve injury-induced structural remodeling and functional activation of microglia in vivo. Systemic delivery of Formoterol inhibits behaviors related to neuropathic pain, such as mechanical hypersensitivity, cold allodynia as well as the aversive component of pain, and reverses chronically established neuropathic pain. Using conditional gene targeting for microglia-specific deletion of β2-ARs, we demonstrate that the anti-allodynic effects of Formoterol are primarily mediated by microglia. Although Formoterol also reduces astrogliosis at late stages of neuropathic pain, these functions are unrelated to β2-AR signaling in microglia. Our results underline the value of developing microglial β2-AR agonists for relief from neuropathic pain and clarify mechanistic underpinnings.
Gesehen am 28.02.2023